Serrivomer sector Garman 1899 - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Serrivomer sector Garman, 1899. Sawtooth Eel . Possibly to 76 cm (30 in) TL (Eschmeyer and Herald 1983). Indo-Pacific; western Pacific Ocean north to Japan (Hatooka in Nakabo 2002); Washington (47°25.8’N) (NWFSC-FRAM) to northern Chile (Fitch and Lavenberg 1968). Depth: 0–4,268 m (13,999 ft) (min.: Robertson et al. 2017; max.: Personal communication: Los Angeles County Museum of Natural History Fish Collection, Los Angeles, California). Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 40, DOI:10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008